Quantitative stereology for fractal dimensions of Aluminum Alloy AA6061 and AA6063 - N. E., Salehudin; Azman, Jalar; Abd. Razak Daud, Daud (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.